Entrepreneurship In Islamic Higher Education (An Analysis of Entrepreneurship Education in the Context of the Independent Campus) - Prasetyo, Muhammad Anggung Manumanoso; Sukatin, Sukatin (Al Irsyad: Jurnal Studi Islam, 2024)
The lack of focus on real business practices and intensive industry partnerships is a major weakness in the current entrepreneurship model at Islamic Higher Education institutions. This study aims to identify an ideal model of entrepreneurship education in higher education. It adopts a qualitative paradigm with a descriptive survey technique, focusing on the State Islamic Institute of Lhokseumawe. This study shows that entrepreneurship education in higher education builds an adaptive ecosystem that enhances graduates' skills, character, and competitiveness, particularly through the Islamic Entrepreneurial Campus and the Independent Learning Independent Campus program. The novelty of this research lies in the integration of the Independent Learning concept with a practical and collaborative entrepreneurship model, emphasizing the development of hard and soft skills aligned with real industry needs. This model introduces curriculum innovation, business partnerships, and direct business activities by students, thereby strengthening market readiness, fostering a culture of innovation, and helping to address unemployment through a holistic and applicable approach. In conclusion, the Independent Learning Independent Campus program supports innovative entrepreneurship programs through entrepreneurial leadership, formal and informal learning, and campus-community partnerships to enhance economic growth and social welfare.